The C291R Tau Variant Forms Different Types of Protofibrils - Karikari, Thomas K.; Thomas, Rachel; Moffat, Kevin G. (Frontiers in Molecular Neuroscience, 2020)
Mutations in the MAPT gene can lead to disease-associated variants of tau. However, the pathological mechanisms behind these genetic tauopathies are poorly understood. Here, we characterized the aggregation stages and conformational changes of tau C291R, a recently described MAPT mutation with potential pathogenic functions. The C291R variant of the tau four-repeat domain (tau-K18; a functional fragment with increased aggregation propensity compared to the full-length protein), aggregated into a mix of granular oligomers, amorphous and annular pore-like aggregates, in native-state and heparin-treated reactions as observed using atomic force microscopy and negative-stained electron microscopy. On extended incubation in the native-state, tau-K18 C291R oligomers, unlike wild type (WT) tau-K18, aggregated to form protofibrils of four different phenotypes: (1) spherical annular, (2) spherical annular encapsulating granular oligomers, (3) ring-like annular but non-spherical, and (4) linear protofibrils. The ring-like tau-K18 C291R aggregates shared key properties of annular protofibrils previously described for other amyloidogenic proteins, in addition to two unique features: irregular/non-spherical-shaped annular protofibrils, and spherical protofibrils encapsulating granular oligomers. Tau-K18 C291R monomers had a circular dichroism peak at ~210 nm compared with ~199 nm for tau-K18 WT. These data suggest mutation-enhanced β-sheet propensity. Together, we describe the characterization of tau-K18 C291R, the first genetic mutation substituting a cysteine residue. The aggregation mechanism of tau-K18 C291R appears to involve β-sheet-rich granular oligomers which rearrange to form unique protofibrillar structures.